Performance and Determining Factors for the Success of the General Election Commission in the 2024 Elections: Kinerja dan Faktor Penentu Keberhasilan Komisi Pemilihan Umum pada Pemilu 2024 - Risna Safariah; Said Zulkifli; Arbainah Saidi; Muhammad Habibi (Academia Open, 2025)
General Background: The performance of electoral management bodies, such as the Indonesian General Election Commission (KPU), is crucial for ensuring democratic and high-quality elections. However, challenges in task execution and inter-divisional coordination often affect effectiveness. Specific Background: In Tana Tidung Regency, North Kalimantan, the KPU faces increased workloads ahead of the 2024 simultaneous elections, while staffing and resources remain limited, potentially hindering smooth operations. Knowledge Gap: While studies on KPU performance exist, empirical research specifically examining factors influencing district-level KPU performance in simultaneous elections is scarce. Aims: This study analyzes the performance of KPU Tana Tidung in the 2024 elections, focusing on quality, quantity, responsibility, cooperation, and initiative, and identifying supporting and inhibiting factors. Results: Using Miles and Huberman’s interactive analysis model, findings show that quality was maintained through effective coordination, communication, and leadership, though some tasks were delayed due to disproportionate workloads. Divisional accountability, cross-division collaboration, and proactive staff initiatives supported performance, while constraints included limited human resources, varied educational backgrounds, voter data validation issues, and inadequate infrastructure. Novelty: This research uniquely identifies district-level KPU performance determinants in simultaneous elections, emphasizing inter-divisional synergy and human resource strengthening. Implications: The study highlights the need to increase staffing and capacity, strengthen coordination, and optimize staff initiative to improve future electoral effectiveness and efficiency. Highlights: Identifies district-level factors influencing KPU performance. Emphasizes inter-divisional cooperation and staff initiative. Recommends strengthening human resources and coordination. Keywords: KPU Performance, Tana Tidung, 2024 Elections, Public Administration, Electoral Management